Aljawari manifestations in Andalusian poetry between influence and impact. (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research represents a vivid image of my neighbors and their manifestations in Andalusian poetry. Juwari was often an inspiration to poets. And they were able to possess the qualities that stirred poets poets poetry. They produced notices for various purposes. The most important of these were nostalgia, complaining, reproach, singing, description, spelling, and heresy: Jawari was not merely an influence in the poetic movement, but influenced the open Andalusian life by expressing their feelings in the form of excerpts required by the place they appeared in.